A CONTRASTIVE ANALYSIS OF SENTENCE FORMATION IN ENGLISH AND LUBUKLINGGAU DIALECT - Sastika Seli (CV Grasta Glory, 2025)
The research aims at explaining some differences between sentence formation in English and Lubuklinggau dialect. Lubuklinggau dialect derives from Palembang Malay language in South Sumatera and as the first and second language in Lubuklinggau. The data was taken from two movies ‘Alternative Math’ in English and ‘Meraih Cita’ in Lubuklinggau dialect. The transcription from oral language to the written form was carried out to analyze the sentence formation in both languages. The data was analyzed by identification, coding, classification, data reduction, description and conclusion drawing. The results show that there are some concerns on the grammatical rule in sentence formation such as copular usage, verb tense, declarative word order, interrogative structure, auxiliary modal use in questions, focus structure, clause embedding and sentence-final particles. Understanding the difference structure between the two languages are expected to improve pedagogical strategies in teaching English as a Foreign Language.